Employees' perception towards the effectiveness of TQM implementation - Christopher, Alex (Universiti Malaysia Sarawak (UNIMAS), 2004)
The purpose of this study was to determine the perception of supporting staffs in government Agency towards the implementation of Total Quality Management. Specifically the objective of the study is to determine the difference among the supporting staffs with varied demographic characteristics such as level of education and length of services. The other objective was to determine the level of effectiveness and relationship between the effectiveness of TQM implementation and other factors such as teamwork, leadership, involvement and training. A survey was conducted in this study for the purpose of data collection. The respondents were 41 supporting staffs in Jabatan Kerja Raya Kuching Divisional Office. Stratified sampling was used to determine the minimum sample size required for the study. The questionnaire consists of three sections. The first part of the question more to the employee selected demography, the second section is more to the employees perception towards the effectiveness of TQM implementation and the third is more to the general opinions toward the TQM implementation. Statistical test such as One Way-ANOVA, Pearson Bivariate Correlation and Linear Regression were used in this study. The study found that 58.5% of the supporting staffs have a positive perception towards the effectiveness TQM implementation; the study also shows that there is no significant difference among the staffs towards the effectiveness TQM implementation. The Pearson Correlation Analysis also indicates that there is significant relationship between the effectiveness TQM implementation and factors such as involvement (r= 0.507, p< 0.001), teamwork (r= 0.620, p<0.001), training (r= 0.386, p< 0.05) and leadership (r= 0.574, p< 0.01). Training (R2= 0.420) and one factor is identified to the most dominant factor using Linear Regression is training factor with the highest R square Based on the findings, it shows that the staffs still have the potential in succeeding in TQM implementation if they continuously sustain the implementation.